Gröbner bases for (partial) flag manifolds. (November 2020) - Petrović, Zoran Z.; Prvulović, Branislav I.; Radovanović, Marko
Abstract: For an arbitrary complex (partial) flag manifold F, a Gröbner basis for the ideal which (in the Borel picture) determines the cohomology algebra H ⁎ ( F ; Z ) is obtained. This Gröbner basis is used to derive multiplication rules for a convenient additive basis of H ⁎ ( F ; Z ) given in terms of Chern classes of the canonical bundles over F . The analogous Gröbner bases related to the mod 2 cohomology of real flag manifolds are also presented.